The "Vendetta di Falconetto" and the "Orlando furioso" (AOQU (Achilles Orlando Quixote Ulysses). Journal on Epic, 2020)
Complementing recent research on Ariosto’s vernacular sources, the present article aims to analyse his possible engagement with a little-known Carolingian poem that has so far escaped the attention of Ariosto scholarship: the longer version of the Vendetta di Falconetto. This article examines the correspondences between the Vendetta and the Furioso, from resemblances between specific episodes to more general thematic and structural affinities. In the end it is suggested that the presence of the Vendetta, whose characters are capable of cynical actions and often break the chivalric code, could perhaps, to some extent, account for some of the most disconcerting elements of the portrayal of chivalry in the Furioso.
Keywords: Vendetta di Falconetto, Orlando furioso, Ariosto, fifteenth-century chivalric tradition; Vendetta di Falconetto; Orlando furioso; Ariosto; Fifteenth-century chivalric tradition